A Fluorimetric Method Based on an Imidazole Compound for Cu2+ Determination in Tap Water - Zafer Ocak (Journal of Chemistry)
Ion sensor properties of 4-(1-(4-hydroxy-3-methoxybenzyl)-1H-benzo[d]imidazol-2-yl)-2-methoxyphenol (L) in acetonitrile-water (1 : 1) were evaluated by fluorescence spectrometry. Pronounced quenching in the fluorescence spectra of the ligand was only observed for the Cu2+ ion among many metal ions. Linear fluorescence responses of the ligand at 360 nm as the function of the Cu2+ concentration were used for the determination of the Cu2+ ion in spiked tap water samples. Recovery values (R%) were satisfactory, and relative standard deviation (RSD%) was below 5.00 in intraday and interday measurements. Detection and quantification limits were 0.28 and 0.84 μg/L, respectively. The assay based on external calibration only took a few minutes.